Government news management - Strategic communication in comparative perspective - Barbara Pfetsch (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
The approach of governments to public information has changed from a rather traditional press release policy - based on interpersonal exchanges between politicians and journalists - to a professionalized and specialized process of strategic communication controlling the flow of news. In the light of this general development, news management is one practical solution for governments to strategically communicate their messages and use the media to further their political and policy goals. The paper explores news management of governments in modern mass democracies from a variety of angles. What is news management? Does news management matter and if so, how is it related to the political process? How is news management organized and how does it vary across different countries? Our assumption is, that the variation in news management, its styles and outcomes across different political systems depend on a series of contextual factors, originating in the political system, the media system and the media culture. The main objective of the paper is to analyze news management and compare the context in which it occurs in three Western democracies: the United States, Great Britain, and Germany. The central argument we propose is that media centered news management is most likely to occur in the United States due to the context of a presidential system, a highly commercialized media system, and the predominance of adversarial journalism . On the other hand, political news management is expected to be the dominant type of strategic communication in Great Britain and Germany. Both European countries not only have parliamentary political systems and strong party governments in common, but also kept a political press and a rather strong public sector television. They also tend to feature a less adversarial working relationship between the government and the media. – – Der Beitrag exploriert den Begriff des News Managementes als strategische Option der politischen Öffentlichkeitsarbeit von Regierungen in modernen Massendemokratien. Was ist News Management? Welchen Stellenwert hat News Management im politischen Prozeß? Wie ist News Management institutionell verankert und wie variieren die Stile des News Management in unterschiedlichen Ländern? Die Annahme des Papiers ist, daß die Stile des News Managementes von einer Reihe von Kontexfaktoren abhängen, die im politischen System, dem Mediensystem und der Medienkultur verankert sind. Der Beitrag analysiert die Ausprägungen des News Management von Regierungen auf der Basis einer Typologie von Mazzoleni für die USA, Großbritannien und Deutschland. Durch den Vergleich läßt sich zeigen, daß die Typen und das Handlungsrepertoire der Informationspolitik nach strukturellen und normativen Kontexten des Regierungssystems und des Mediensystems variieren. In den USA herrscht ein medienorientierter Stil von News Management vor, der durch die Kontextfaktoren eines präsidentiellen Regierungssystems, einer fast vollständig kommerzialisierten Medienlandschaft sowie der Philosphie des ,,adversarial journalism“ zu begründen ist. Demgegenüber dominieren in Großbritannien und Deutschland politische Stile des News Management, die mit den Kontextfaktoren eines parlamentarischen Regierungssystems und einer starken Rolle politischer Parteien sowie durch die Existenz einer politischen Presse und eines öffentlich-rechtlichen Rundfunks in Zusammenhang gebracht werden können.
Keywords: 300